2022
DOI: 10.1177/17455057221133835
|View full text |Cite
|
Sign up to set email alerts
|

Level and predictors of breast cancer awareness among Saudi women: A nationwide study

Abstract: Background: Breast cancer occurs when abnormal breast cells grow rapidly and uncontrollably. Early detection and intervention have been established to significantly decrease mortality rates. Objective: There is a lack of focused research investigating the degree of breast cancer awareness among Saudi women. Thus, this study aimed to fill this gap by conducting a nationwide survey on a large pool of women. Design: A cross-sectional web-based nationwide study. Methods: This study targeted Saudi women from all re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Additional effort should be put forth through women’s healthcare providers to increase the awareness of breast cancer screening. That means we need to continue emphasizing the importance of primary healthcare for early detection of breast cancer in the early stages Qedair 2022 18 430 1855 Our study reports an alarmingly high level of poor overall breast cancer awareness in Saudi women. Interventions should be implemented to combat this lack of awareness Al-Khamis 2018 25 27 263 We are reporting a major gap in breast cancer awareness and several logistic and emotional barriers to seeking medical care among adult Saudi women.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Additional effort should be put forth through women’s healthcare providers to increase the awareness of breast cancer screening. That means we need to continue emphasizing the importance of primary healthcare for early detection of breast cancer in the early stages Qedair 2022 18 430 1855 Our study reports an alarmingly high level of poor overall breast cancer awareness in Saudi women. Interventions should be implemented to combat this lack of awareness Al-Khamis 2018 25 27 263 We are reporting a major gap in breast cancer awareness and several logistic and emotional barriers to seeking medical care among adult Saudi women.…”
Section: Resultsmentioning
confidence: 91%
“…The individual study sample sizes ranged from 137 to 2,544 participants. 18 , 23 Specifically, five studies targeted the general population, 18 , 20 , 23 , 25 , 26 while five studies focused on patients. 19 , 22 , 24 , 27 , 28 Additionally, three studies specifically examined schoolteachers as their target population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Occupation’s impact lessened when adjusted for other variables. Qedair et al [ 30 ] showed regional, income, and employment status differences in breast cancer awareness. Tailored campaigns addressing demographic nuances are essential for bridging knowledge gaps.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study yielded alarming results regarding Saudi women's awareness of BC, perception of risk factors, and preventive measures. 2 A high incidence of BC was observed in central and western Saudi Arabia, 3 with more deterioration mortality and morbidities are expected in Saudi Arabia. 4 Reasonable beliefs and awareness of warning signs for breast cancer prevention will enable women and their families to develop ideas about breast cancer prevention.…”
Section: Introductionmentioning
confidence: 99%